Cómo Salir con un Mexicano Volador : Relatos Nuevos y Escogidos - Olivas, Daniel A. (Book collections on Project MUSE., 2022)
"Cómo salir con un Mexicano volador : Relatos nuevos y escogidos by Daniel A. Olivas was originally published in English in 2022 as How to date a flying Mexican : new and collected stories by the University of Nevada Press. The English text has been reproduced in Spanish and the front matter has been modified to reflect the new translation"--